2007
DOI: 10.1007/s10616-007-9077-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of progenitor cells from cord blood using adhesion matrices

Abstract: The aim of this study was to develop optimal conditions for selective adhesion and isolation of mesenchymal progenitor cells (MPCs) from cord blood and to determine their potential for osteogenic differentiation. Mononuclear cells (MNCs) were isolated by Ficoll-Paque gradient and plated onto 48-well culture plates precoated with: human or bovine collagen type I, human collagen type IV, fibronectin or matrigel. Cultures were incubated in aMEM containing fetal calf serum. Viability of the adherent cells was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This result may be explained by the fact that expression of osteocalcin is not correlated with the degree of cytochemical stains like AR, AP and VK (Sudo et al 2007). Therefore, an alternative solution was adopted suggested by Maurice et al (2007) who asserted that the enrichment of vitamin D 3 and FGF9 in their osteogenic medium was essential for the positive expression of osteocalcin. This finding was corroborated by other studies which stated that in vitro differentiation of embryonic stem cells (ES) and MSCs need a few important factors, among them are ascorbic acid, dexamethasone and 1,25 dihydroxyvitamin D 3 , essential elements for matrix deposition and mineralization (Purpura et al 2004;Duplomb et al 2007;Jono et al 1998;Long et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result may be explained by the fact that expression of osteocalcin is not correlated with the degree of cytochemical stains like AR, AP and VK (Sudo et al 2007). Therefore, an alternative solution was adopted suggested by Maurice et al (2007) who asserted that the enrichment of vitamin D 3 and FGF9 in their osteogenic medium was essential for the positive expression of osteocalcin. This finding was corroborated by other studies which stated that in vitro differentiation of embryonic stem cells (ES) and MSCs need a few important factors, among them are ascorbic acid, dexamethasone and 1,25 dihydroxyvitamin D 3 , essential elements for matrix deposition and mineralization (Purpura et al 2004;Duplomb et al 2007;Jono et al 1998;Long et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Human MSCs have been isolated from various sources, such as adipose tissues, bone marrow (BM), umbilical cord blood (UCB), amniotic fluid, amniotic placenta, scalp tissue, amniotic membrane, and synovial tissue (Chao et al 2004;Koc and Lazarus 2001;Xu et al 2004;Minguell et al 2001;Song and Tuan 2004;Goodwin et al 2001;Rosada et al 2003;Kogler and Wernet 2006;Riordan et al 2007;Koblas et al 2005). Functional analysis has confirmed that they share a core of gene expression profiles (Musina et al 2007;Tsai et al 2007;Reddi 2006;Tuan and Chen 2006;Chang et al 2006;Maurice et al 2007;de Bari and Dell'Accio 2007;Liu et al 2007). MSC cultures in vitro are characterized by homogeneous colonies with a typical fibroblast spindle like shape Bieback et al 2004;Minguell et al 2001).…”
Section: Multipotent Mesenchymal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanism linked to transcriptor activators activity is mediated by histone acetyltransferases (HATs) which increase the target gene expression, conversely the transcriptor reversors are linked to histone deacetylases which downregulate target gene expression (HDACs) (Maurice et al 2007). There are a few members of HDAC family, HDAC3-4-5, that have been shown to be able to interact with Runx2, inhibiting its transcriptional activity in osteoblast differentiation process, particularly, HDAC 4 or 5 which are involved in TGF-b/ Sma and mad-related protein (Smad) and mediating the inhibition of Runx in osteogenesis and mineralization .…”
Section: Bone Regeneration By Using Osteoblast From Hbm Mscsmentioning
confidence: 99%